A Development of moisture resistant lightweight material from cullet and fly ash - T.saengchantara, Wanna; Sriprasertsuk, Sutthima; Suwannason, Phatthiya; Suwannason, Phatthiya (Bulletin of Applied Sciences, 2016)
The large amount of cullet and fly ash affect Thailand's environment. The objective of this study is to develop a moisture resistant lightweight material from cullet and fly ash. The crushed cullet was sieved through 200 mesh, as well as the fly ash. The compositions consisted of 50-80% cullet, 20-50% fly ash, together with dolomite and limestone as foaming agents, sodium silicate as a binder, and borax as a fluxing agent. The mixture was mixed and put into the fired clay mold sized 100 x 100 x 25 mm.3 The mixture was fired in an electric kiln at 800°C with a heating rate of 2.5°C/ min. The sample properties were evaluated including appearance, density and compressive strength. The formulas which had low density and high compressive strength were then prepared for the prototype products. The prototypes properties were evaluated including density, compressive strength, water absorption, heat conductivity, and moisture resistance. The results showed that 60% cullet and 40% fly ash formula had density 690 kg/m3, compressive strength 6.84 MPa, water absorption 24.84 %, heat conductivity 0.119 watt/m.K and resistant to moisture. The sample can be used as a building insulating material.